Buprenorphine patches: impact on cognitive functions in Down's syndrome. Issue 3 (13th August 2019) - Javaid, Amir; Senior‐Kemp, Emily; Southern, Chloe; Connor, Michelle; Michael, Gabriel
Abstract : Opioids have been regarded as among the most effective medications for the treatment of acute, chronic severe pain and cancer pain. However, the longterm administration of opioids continues to be controversial. There are concerns surrounding misuse, abuse and addiction.1 Dr Javaid et al report of a case of a woman with Down's syndrome and severe learning disability presenting with symptoms of dementia, due to the possible likelihood of prolonged use of buprenorphine patches, over the five years. These findings highlight the need for regular medication reviews for individuals with learning disabilities.